Knowledge, attitude and practices toward pharmacovigilance and adverse drug reactions in postgraduate students of Tertiary Care Hospital in Gujarat - Het B Upadhyaya; Mukeshkumar B Vora; Jatin G Nagar; Pruthvish B Patel (Wolters Kluwer Medknow Publications, 2015)
Being key health care professional, physicians, pharmacist and nurses have immense responsibility in reporting adverse drug reaction (ADR). Therefore, the study objective was to evaluate the knowledge, attitude and practices (KAP) toward pharmacovigilance and ADRs of postgraduate students of our institute. A cross-sectional questionnaires based study was carried out in postgraduate students of the clinical department at tertiary care hospital attached with Govt. Medical College, Vadodara, Gujarat (India). A total of 22 questionnaires about KAP toward ADRs and pharmacovigilance were developed and peer viewed of all questionnaires by expert faculties from our institute. We were contacted directly to postgraduate students of respective clinical department; questionnaires were distributed and taken back after 30 min. The filled KAP questionnaires were analyzed in question wise and their percentage value was calculated by using Microsoft Excel spreadsheet. Postgraduate residents (n = 101) from different clinical departments were enrolled in the study. Average 34.83% correct and 64.08% incorrect knowledge about ADRs and pharmacovigilance and an average 90.76% students were agreed to reporting ADRs is necessary, mandatory and increased patient's safety. Only 7.92% of postgraduate doctors were reported ADR at institute or ADR reporting center. We concluded that postgraduate students have a better attitude toward reporting ADRs, but have lack of knowledge and poor practices of ADRs. The majority of postgraduate students were felt ADR reporting and monitoring is very important, but few had ever reported ADRs because of lack of sensitization and knowledge of pharmacovigilance and ADR.